EFFECT OF K AND Ca APPLICATION ON SOME PHYSIOLOGICAL AND BIOCHEMICAL PARAMETERS AND MITIGATION OF SALT STRESS OF SOME WHEAT GENOTYPES GROWN IN HYDROPONIC - & Al–Mosawy, Al-Yesari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted to study the role of potassium and calcium mixture to mitigate salt stress of some genotypes of wheat to improve growth and yield of wheat the enzymatic situation and root architecture, this experiment included three factors the first factor was three levels of potassium and calcium K50+Ca100, K100+Ca200 and K200+Ca400 µM.L-1, and the second factor was three levels of salinity 0NaCl and 20 NaCl and 40µM.L-1NaCl, and the third factor was four varieties of wheat namely: with three replications.The result can be summarized as follow: Abu Ghraib3 variety was superior in diameter of root and the activity of some antioxidant enzymes SOD in shoot. Ibaa 99 variety was superior in root weight and root length and the activity of some antioxidant enzymesPOD,CAT, proline concentration, Jandola variety was superior root weight and root length and the activity of some antioxidant enzymes SOD, SinAl-Fil was superior in the activity of some antioxidant enzymes POD, CAT and proline concentration. K50+Ca100 treatment was superior in the activity antioxidant enzymes POD, CAT, SOD, proline concentration. While K100+Ca200 treatment was superior in root length, K200+Ca400 treatment was superior in root diameter and root weight. 40NaCl treatment was superior in the activity of antioxidant enzymes POD,CAT,SOD, proline concentration. 0NaCl treatment was superior in root diameter and root weight. and found that the addition of calcium and potassium to the nutrient solution worked to reduce stress resulting from the salt added sodium chloride were inferred through the results obtained.